PEMANFAATAN INFORMATION AND COMMUNICATIONS TECHNOLOGY (ICT) DALAM PENULISAN KARYA ILMIAH : STUDY LITERATURE - Ninin Kurike R; Agus Setiawan; Rama Wijaya Abdul Rozak (STKIP Subang, 2024)
ABSTRACT This study discusses the use of Information and Communication Technology (ICT) in writing scientific papers. The main objective of this study is to explore and analyze how the use of ICT can be integrated effectively to help facilitate writing scientific papers with the Publish or Perish, Vos Viewer and Mendeley platforms. This study uses a Systematic Literature Review (SLR). In order to save space, this article will present data obtained from 25 journals that have met the in-depth inclusion criteria for publications in the last 10 years to determine the use of ICT in writing scientific papers. The results of the study show that the use of Information and Communication Technology (ICT) such as Publish or Perish (PoP), Vos Viewer, and Mendeley has made it easier for researchers and students to write scientific papers. PoP helps search and analyze academic journals and citation data, Vos Viewer allows bibliometric mapping to understand research trends, and Mendeley facilitates reference management and prevents plagiarism. These applications improve the efficiency of literature searches, citation accuracy, and the quality of scientific papers, and support more structured and systematic writing. The use of ICT ensures higher quality and more reliable research. Keywords: Utilization of ICT, Scientific Work, Publish or Perish, Vos Viewer, Mendeley ABSTRAK Penelitian ini membahas pemanfaatan Information and Communication Technology (ICT) dalam penulisan karya ilmiah. Tujun utama penelitian ini adalah mengeksplorasi dan mengaalisis bagaimana pemanfaatan ICT dapat diitegrasikan ecara efektif untuk membantu mempermudah penulisan karya ilmiah dengan platfrorm Publish or Perish, Vos Viewer dan Mendeley. Penelitian ini menggunakan Systematic Literature Review (SLR). Demi menghemat ruang, artikel ini akan menyajikan data yang diperoleh dari 25 jurnal yang telah memenuhi kriteria inklusi mendalam terhadap publikasi 10 tahun terakhir untuk mengetahui pemanfaatan ICT dalam penulisan karya ilmiah. Hasil penelitian menunjukan bahwa Pemanfaatan Teknologi Informasi dan Komunikasi (ICT) seperti Publish or Perish (PoP), Vos Viewer, dan Mendeley telah mempermudah peneliti dan mahasiswa dalam penulisan karya ilmiah. PoP membantu mencari dan menganalisis jurnal akademik serta data sitasi, Vos Viewer memungkinkan pemetaan bibliometrik untuk memahami tren penelitian, dan Mendeley memudahkan pengelolaan referensi serta mencegah plagiarisme. Aplikasi-aplikasi ini meningkatkan efisiensi pencarian literatur, keakuratan sitasi, dan kualitas karya ilmiah, serta mendukung penulisan yang lebih terstruktur dan sistematis. Pemanfaatan ICT memastikan penelitian yang lebih berkualitas dan terpercaya. Kata Kunci: Pemanfaatan ICT, Karya Ilmiah, Publish or Perish, Vos Viewer, Mendeley